Entrepreneurship, innovation and business competitiveness in the service-producing sector: implementation to mainland Portugal - Pereira, Orlando P. (2012)
One of the most important factors of future regional development is the establishment of companies. There are, however, certain sectors wherein entrepreneurship might reveal itself to be strategic. This is the example of Knowledge intensive business services (KIBS) as leading vehicles for technological progress, of innovation as well as economic growth, all of which deemed to be strategic for the development of businesses and industry in the region where they are set. Since these are based on knowledge, they are located in urban areas and are considered as an essential element of the innovation system of big cities. These stand simultaneously as suppliers of innovation capacity for small companies and for those companies where I&D is null or of low significance. KIBS are not standardized as they are created for each particular situation to suit the needs of clients. These are inherently intangible in view of their knowledge intensity, therefore difficult to store and to transport. High levels of competency and confidence are demanded even though the sector presents asymmetric information, placing the client in a position of not being able to rigorously assess the quality of the service rendered.